Enhancing Classroom Management Through Student Agency In Early Childhood Education (PIAUD IAIN Kudus, 2025)
This paper explores how student agency relationships take an important role in creating good and effective classroom management, especially when applied in building class agreements through collaborative processes by class members in Early Childhood Education. The background question of this paper is